The role of innate immunity in diabetic nephropathy and their therapeutic consequences - Min Yang; Chun Zhang (Elsevier, 2024)
Diabetic nephropathy (DN) is an enduring condition that leads to inflammation and affects a substantial number of individuals with diabetes worldwide. A gradual reduction in glomerular filtration and emergence of proteins in the urine are typical aspects of DN, ultimately resulting in renal failure. Mounting evidence suggests that immunological and inflammatory factors are crucial for the development of DN. Therefore, the activation of innate immunity by resident renal and immune cells is critical for initiating and perpetuating inflammation. Toll-like receptors (TLRs) are an important group of receptors that identify patterns and activate immune responses and inflammation. Meanwhile, inflammatory responses in the liver, pancreatic islets, and kidneys involve inflammasomes and chemokines that generate pro-inflammatory cytokines. Moreover, the activation of the complement cascade can be triggered by glycated proteins. This review highlights recent findings elucidating how the innate immune system contributes to tissue fibrosis and organ dysfunction, ultimately leading to renal failure. This review also discusses innovative approaches that can be utilized to modulate the innate immune responses in DN for therapeutic purposes.